These/media/appropriated:indigenous storytelling of patience, identity and politics - Rincón, Omar (Folios, revista de la Facultad de Comunicaciones y Filología, 2010)
Searching to find others ways to communicate, we found that Indigenous communication practices can teach us how to storytell/politicize/subvert communication’s status quo. And we keep hearing their teachings, their stories. Based on the certainty that they will always be on the planet, Indigenous peoples have the patience to search and find tactical ways to transform a camera or a story into political activism, into ways to subvert the mainstream media logics, into agency to revive their own cultural identities. In this free essay I intend to reflect looking into an “indigenous mirror.” We hope that the time is ripe to be able to listen to indigenous media, to dare to be different.